Efecto del formol y extracto acuoso de las hojas de Mansoa alliacea “ajos sacha” en el control de parásitos monogeneos presentes en adultos de Otocinclus affinis, Iquitos-Perú, 2018 - Chuquipiondo Guardia, Carlos Tobias (2019)
With the objective of evaluating the effect of formalin and the aqueous extract of the leaves of Mansoa alliacea "ajos sacha" (EAHAS) in the control of monogeneous parasites present in adults of Otocinclus affinis, parasitological examinations were carried out on 400 specimens, analyzing skin, fins and gills; the monogeneans were fixed in permanent sheets using the Gray & Wess method, and their parasitic indices were determined: prevalence, average intensity, average abundance. For the bioassay of the lethal median concentration (LC50-96h), 720 specimens were used, distributed in a completely random design, in 6 treatments with 3 repetitions, evaluating the formalin concentrations (0, 0.05, 0.1, 0.15, 0.2 and 0.25 mL/L) and the EAHAS (0.5, 15, 25, 35, 45 mL/L). For the efficacy bioassay of formalin and Mansoa alliacea "ajos sacha" leaf extract (EAHAS) in controlling monogeneans, a total of 640 adults of O. affinis were used, distributed in a completely random design, in 16 treatments with 2 repetitions, formalin concentration (0.01, 0.02 and 0.03 mL/L), EAHAS (1, 3, 5 mL/L) and their combination were evaluated, in 24h baths, for a period of 5 days . In both bioassays, the quality of the water (temperature, oxygen and pH) was monitored. Three monogenean parasites were identified: Gyrodactylus sp.n. Demidospermus sp.n. and Unilatus sp.n.; registering high parasitic indices in the first species. The estimated LC50 at 96 h for formalin and EAHAS was 0.1 mL/L and 14.01 mL/L (with 95% confidence). Efficacy in monogeneous control and greater survival of fish were recorded in treatments T6 (0.03 mL formol/L), T8 (1mL EAHAS/L + 0.02 formo/L) and T9 (1mL EAHAS/L + 0.03 formo/L).